Excessive daytime sleepiness in myotonic dystrophy: a narrative review - Hoxhaj, Domeniko; Pascazio, Alessia; Maestri, Michelangelo; Ricci, Giulia; Fabbrini, Monica; Torresi, Francesca Buracchi; Siciliano, Gabriele; Bonanni, Enrica (Frontiers in Neurology, 2024)
Introduction Excessive daytime sleepiness (EDS) is a common and debilitating symptom in both forms of myotonic dystrophy (DM), significantly impacting patients’ quality of life. The review focuses on the purpose of examining the current understanding of EDS in these conditions, the difficulty in correctly accessing it, the recent findings related to its etiology and prevalence, and a summary of potential therapeutic implications. Methods We conducted a comprehensive search through PubMed, selecting studies that provided significant insights into the mechanisms, prevalence, and management of EDS in DM1 and DM2. Results and discussion EDS is highly prevalent in both DM1 and DM2. Polysomnographic studies have revealed prominent dysregulation of REM sleep in DM1, suggesting a possible narcoleptic-like phenotype and alterations in NREM sleep that contributes to daytime sleepiness. Other factors have been proposed to explain EDS in DM1, including dysregulation of the sleep-wake circadian rhythm through nocturnal actigraphy analysis. The central origin of EDS is increasingly delineated supported by serotonin and orexin pathways dysfunction, and recent neuroradiological findings showing that in DM1 hippocampus volume was positively correlated with self-reported fatigue and somnolence. Sleep-disordered breathing and respiratory dysfunctions are prevalent in DM, their direct correlation with EDS remains complex and inconclusive, but respiratory evaluation should be recommended if obstructive sleep apneas or respiratory muscle dysfunctions are suspected. Drug interventions, such as modafinil and mexiletine, have shown promise in managing excessive daytime sleepiness and reducing myotonia without significant cardiac conduction effects. Enhancing EDS management in myotonic dystrophy is key to improving overall patient well-being.